Islamic Counseling as a Therapy to Reduce Impulsive Behavior In Autism Children - Dilla Astarini; Hermi Pasmawati (An-Nadwah, 2023)
This study aims to analyze in depth the effectiveness of Islamic counseling carried out by counselors in reducing impulsive behavior in autistic children. Research Methods were used qualitatively with a case study approach. The informant selection technique uses purposive sampling techniques, so that two core informants are obtained, namely DS and DT and four accompanying informants.Dat collection techniques use interviews, observations, documentation studies, and literature studies. Data analysis techniques go through six stages, namely collection, refinement, processing, analysis, analysis process, and data conclusion. Research findings show that Islamic counseling is effective as a therapy in reducing impulsive behavior in autistic children, as can be seen from the picture of significant changes in the behavior of autistic children. BS and DT become more compliant and able to be cooperative in the learning process, although they still need special assistance when BS and DT explore their potential during learning hours. BS informants still show the behavior of hitting goods or tables, but the intensity is only occasional. The behavior of hitting the head, wrinkling fingers, and playing with saliva does not appear at all. For DT informants the behavior of hitting surrounding goods still appears, but the intensity is only occasional. The emotions displayed are not as explosive as they used to be, only at the time of the class boss. Meracau only occasionally appears. The behavior of attacking and walking around in the classroom shouting did not appear. Recommendations for counselors in inclusive schools can use Islamic counseling therapy in reducing impulsive behavior in autistic children.